the locus of the mid pt. of a chord of the circle x2 +y2 =4,which subtend a right angle at the origin is:

3 years ago


Answers : (1)


radius of circle=2

so length of chord=2√2

let O be origin and P be mid-point of chord


so locus is x2+y2=2

3 years ago

Post Your Answer

More Questions On Analytical Geometry

Ask Experts

Have any Question? Ask Experts
Post Question
Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details
Find the arithmetic mean of the ordinates of the feet of the normals from the point (3,5) to the parabola y^2 = 8x
Sum of the ordinates of conormal points is zero. we can prove by following approach: Equation of normal at any point(2t^2,4t) to the parabola y^2=8x is y= -ty+4t+2t^3 it passes through (3,5)...
Sunil Raikwar 5 months ago
Angle between pair of Staines x^2+2xy-y^2 is?
Dear student, If we compare this with the standard equation: ax 2 +2hxy+by 2 =0 We get, a =1, h = 1, b = -1 Hence using the formula: we get: Hence, Regards Sumit
Sumit Majumdar 6 months ago
Q . EQUATION OF THE STRAIGHT LINE BELONGING TO THE FAMILY OF LINES :- ( x + y ) + k( 2x – y +1) =0 , THAT IS FARTHEST FROM ( 1 , – 3) IS :- 13y – 6x = 7 13y + 6x = 0 15y + 6x =7 15y – 6x = 7
The point of intersection of given family of lines is the point of intersection of x+y=0 and 2x-y+1=0 and it is (-1/3 1/3). The required line belongs to the given family so it must pass...
Himaja one month ago it
bharat makkar one month ago
If sinx+siny=root3(cosy-cosx) Prove that sin3x+sin3y=0.
Hello students, please check the solution of your question given below: sinx+siny = root3 ( cosx-cosy) 2sin(x+y/2)cos(x-y/2) = root3 {2sin(x+y/2)sin(y-x/2)} sin(x+y/2)[cos(x-y/2)-root3....
Sunil Raikwar 5 months ago
Dear student, According to the given relation, we would have: If we multiply both sides by a factor of 4, we get: This on simplifying gives us: If the right hand side can be simplified to...
Sumit Majumdar 5 months ago
The locus of the point z satisfying the condition arg (Z-1)/(Z+1)=Pi/3
Transform the arg [(z-1)/(z+1)]=pi/3 into (z-1)/(z+1)=tan pi/3 Solve this eqn for z.. It will give a linear eqn. solution....
Ravi 2 months ago
if value of 1+∑ n=1 51 (4n 2 +2n-1)((2n-1)!)=(53+a)! then a is equal to
Hi, U need to rewrite this equation extensively. Split the quadratic into 2n.2n and 2n-1 So when u multiply the factorial ull get 2n.2n.(2n-1)! + (2n-1)[(2n-1)!] I can write like...
Yash Baheti 2 months ago
View all Questions »